Two dimensional superconductors in electrides. (7th December 2017) - Ge, Yanfeng; Guan, Shan; Liu, Yong
Abstract: Two-dimensional (2D) superconductors are always a research hotspot in superconductivity, due to the huge importance of 2D superconductors in quantum phenomena transitions. And the natural metallic 2D electride with exceptional physical properties is one member of candidate materials for 2D superconductors in the Bardeen–Cooper–Schrieffer theory. The properties of electron–phonon induced superconductivity in 2D electrides, Y2 C and MgONa, are investigated by using first-principles calculations. Because of the weak electron–phonon coupling between surface electronic states and phonons, critical temperature of the prototypical Y2 C and MgONa are estimated to be 0.9 K and 3.4 K, respectively. It is also found that the electronic doping can improve superconductivity to T c = 2.4 K and 4.5 K, resulting from the increase of density of states and the coupling between inner-layer electrons and phonons. In addition, a small tensile strain can enhance the critical temperature of MgONa to 6.15 K@n 2 D e = 5.5 × 10 14 cm −2, due to the increase of density of states and phonon softening.